Interpreters in law enforcement contexts: Practices and experiences according to investigators. Issue 2 (7th February 2018) - Shaffer, Sarah A.; Evans, Jacqueline R.
Summary: Interpreters play an important role in the criminal justice system, yet little is known about the way interpreters are used. This survey of U.S. law enforcement ( N = 299) assessed practices and perceptions regarding interpreter use during interviews with nonnative English speakers. Investigators reported using colleagues more often than professional interpreters, using interpreters more often with suspects and in certain crimes (e.g., domestic violence), and that interpreters are usually at least partially informed about case facts prior to translating. Investigators responded to experimental vignettes, and results indicated they were more likely to seek and obtain interpreters when an interviewee has lived in the United States for fewer years; however, the language spoken and the interviewee's role (e.g., witness vs. suspect) did not affect decisions to request an interpreter. Several avenues for future experimental research are identified and discussed, including interpreting over the phone and interpreter susceptibility to biases.